Sex differences in lucid dreaming incidence - Gackenbach, Jayne (My University, 1981)
John Palmer wrote in 1980, that, “females were slightly more likely than males to have lucid dreams in both sub—samples, but the differences were not significant(11/10/81).”Both Hearne and Gackenbach have found this difference to be significant in their student samples.
Keywords: dreams; sex differences